Critical roles of IL-33/ST2 pathway in neurological disorders - Abd Rachman Isnadi, Mohammad Faruq; Chin, Voon Kin; Abd. Majid, Roslaini; Lee, Tze Yan; Abdullah, Maizaton Atmadini; Omenesa, Ramatu Bello; Ibraheem, Zaid Osamah; Basir, Rusliza (Hindawi, 2018)
Interleukin-33 (IL-33) is an IL-1 family member, which exhibits both pro- and anti-inflammatory properties solely based on the type of the disease itself. Generally, IL-33 is expressed by both endothelial and epithelial cells and mediates its function based on the interaction with various receptors, mainly with ST2 variants. IL-33 is a potent inducer for the Th2 immune response which includes defence mechanism in brain diseases. Thus, in this paper, we review the biological features of IL-33 and the critical roles of IL-33/ST2 pathway in selected neurological disorders including Alzheimer’s disease, multiple sclerosis, and malaria infection to discuss the involvement of IL-33/ST2 pathway during these brain diseases and its potential as future immunotherapeutic agents or for intervention purposes.